Details of the Rangamandapa’s Shikhara - Temples of India Project Team (Jio Institute, 2024)
The west pediment on the shikhara (superstructure) of the separate rangamandapa (an open type of pillared hall used for ceremonial rituals) depicts the trinity. At the centre, Shiva is depicted in his Bhairava form, flanked by Vishnu on his right and Brahma on his left side. There are two other gods, one on each end. The trinity is shown seated while the other two gods are shown standing. A six-armed Bhairava is shown holding his multiple attributes and his aggressive aspect is shown through his fangs. A four-armed Vishnu is shown with his attributes, seated on Garuda and Bramha is also shown seated, holding his attributes. The other two gods are also four-armed and hold their respective attributes.